COMPARISON OF SCIENCE LITERACY LEVELS IN STUDENTS™ BIOLOGY TEXTBOOKS IN UNITED KINGDOM, MALAYSIA, AND INDONESIA ON THE TOPIC OF RESPIRATORY SYSTEM - Ujung, Siti Nuraisah Asma (Universitas Negeri Medan, 2024)
This research aims to compare scientific literacy levels in textbooks from three different publishers in three countries. This study is a qualitative approach with a content or document analysis method by describing the level of science literacy of biology textbooks based on aspects of science literacy. Samples were obtained from Indonesia™s textbooks from Erlangga publisher, Malaysia™s textbook from UG Press Sdn, Bhd, and Cambridge publisher. The result shows that the aspect of science as a body of knowledge has the highest average of 67.40% (good), the aspect of science as a way of investigating with the average of 21.31% (deficient), the aspect of science as a way of thinking with the average of 21.31% (deficient), the aspect interaction of science, technology, and society with the average of 6.66% (poor).